Total Hip Arthroplasty Concomitant with Patellofemoral Arthroplasty and Medial Patellofemoral Ligament Reconstruction for a Patient with Patellar Dislocation Combined with Hip Dysplasia: A Case Report of a Successful Outcome at 5-Year Follow-Up - Takuya Iseki; Tomoya Iseki; Shohei Okahisa; Shinichi Yoshiya; Shigeo Fukunishi; Toshiya Tachibana (Case Reports in Orthopedics, 2021)
Background. Posttraumatic patellar dislocation is rare, and consistent surgical strategy therefore has not been defined due to multifactorial factor. In this case study, we treated a case of a patellar dislocation with hip osteoarthritis and increased femoral anteversion by performing a two-staged surgery. In the first stage, total hip arthroplasty was performed, and in the second stage, simultaneous patellofemoral arthroplasty and medial patellofemoral ligament reconstruction using semitendinosus tendon autograft were performed. Case Report. A 56-year-old female patient who previously had right hip osteoarthritis complained of right knee pain after a fall. Radiographic examination showed lateral dislocation of the patella with osteoarthritic (OA) change in the patellofemoral joint and an excessive femoral anteversion with OA change on the right hip joint. Total hip arthroplasty was performed firstly to decrease femoral anteversion. Then, simultaneous patellofemoral arthroplasty and medial patellofemoral ligament reconstruction was performed for residual patellar dislocation and patellofemoral OA without tibiofemoral joint OA. At the time of the 5-year follow-up after surgery, the patient was able to walk with a wheelbarrow without any complications. Conclusion. To the best of our knowledge, this is the first case of a patellar dislocation with an increased femoral anteversion and patellofemoral OA treated by a combination of total hip arthroplasty, patellofemoral arthroplasty, and medial patellofemoral ligament reconstruction. The clinical outcome improved at 5 years after these surgeries. Therefore, these surgical options can be considered to be useful.